Grain refinement of AZ91D magnesium alloy by MgCO3 - Chen,Ti Jun (2011)
The grain refining technique of AZ91D magnesium alloy by MgCO3 has been investigated. The refining mechanism and tensile properties of the resulting alloy have also been discussed. The results indicate that MgCO3 can decrease its grain size from 311 to 53µm. Correspondingly, the tensile properties are obviously improved. The higher the cooling rate from addition temperature to pouring temperature or the higher the addition temperature, the finer the grains. The melt treated by MgCO3 should be poured as soon as possible because the inoculation fading is quite quick. The microstructure sensitivity to the diameter of a cast rod is relatively high and the microstructures of the rods with large diameters are quite inhomogeneous. The refining mechanism of MgCO3 belongs to heterogeneous nucleation and the nucleant substrates are believed to be the Al4C3 particles formed from the reactions between the MgCO3 and the molten alloy.